Short- and Long-Term Recovery after Moderate/Severe AKI in Patients with and without COVID-19. Issue 2 (24th February 2022) - Sun, Siao; Annadi, Raji R.; Chaudhri, Imran; Munir, Kiran; Hajagos, Janos; Saltz, Joel; Hoai, Minh; Mallipattu, Sandeep K.; Moffitt, Richard; Koraishy, Farrukh M.
Key Points: Respiratory disease was associated with nonrecovery and renal recovery was associated with survival in AKI-2/3 patients with COVID-19. Machine Learning algorithms can predict AKI and recovery from COVID-19-associated AKI-2/3 and identify key predictors. At 12-month follow-up in moderate/severe AKI survivors, no difference in CKD between COVID-positive and -negative patients was observed. Visual Abstract: Abstract : Background: Severe AKI is strongly associated with poor outcomes in coronavirus disease 2019 (COVID-19), but data on renal recovery are lacking. Methods: We retrospectively analyzed these associations in 3299 hospitalized patients (1338 with COVID-19 and 1961 with acute respiratory illness but who tested negative for COVID-19). Uni- and multivariable analyses were used to study mortality and recovery after Kidney Disease Improving Global Outcomes Stages 2 and 3 AKI (AKI-2/3), and Machine Learning was used to predict AKI and recovery using admission data. Long-term renal function and other outcomes were studied in a subgroup of AKI-2/3 survivors. Results: Among the 172 COVID-19-negative patients with AKI-2/3, 74% had partial and 44% complete renal recovery, whereas 12% died. Among 255 COVID-19 positive patients with AKI-2/3, lower recovery and higher mortality were noted (51% partial renal recovery, 25% complete renal recovery, 24% died). On multivariable analysis, intensive care unit admission and acute respiratory distress syndrome were associated with nonrecovery, and recovery was significantly associated with survival in COVID-19-positive patients. With Machine Learning, we were able to predict recovery from COVID-19-associated AKI-2/3 with an average precision of 0.62, and the strongest predictors of recovery were initial arterial partial pressure of oxygen and carbon dioxide, serum creatinine, potassium, lymphocyte count, and creatine phosphokinase. At 12-month follow-up, among 52 survivors with AKI-2/3, 26% COVID-19-positive and 24% COVID-19-negative patients had incident or progressive CKD. Conclusions: Recovery from COVID-19-associated moderate/severe AKI can be predicted using admission data and is associated with severity of respiratory disease and in-hospital death. The risk of CKD might be similar between COVID-19-positive and -negative patients.